2014
DOI: 10.1017/s0007485314000200
|View full text |Cite
|
Sign up to set email alerts
|

Differences in sperm storage and remating propensity between adult females of two morphotypes of theAnastrepha fraterculus(Diptera: Tephritidae) cryptic species complex

Abstract: The South American fruit fly, Anastrepha fraterculus, is a complex of cryptic species composed of at least seven morphotypes. Some of them, such as the Peruvian and Brazilian 1 morphotypes (which include Argentinean populations), exhibit strong pre-copulatory isolation, yet it is possible to obtain heterotypic crosses when forcing copulation of adults under laboratory conditions. The cross involving Peruvian males and Argentinean females produces F1 offspring with reduced viability in terms of egg hatch. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 41 publications
1
11
0
3
Order By: Relevance
“…The interpretation of the results in the case of D. melanogaster assumes that copulation duration is under male control (MacBean & Parsons ), while in our case, crosses between different morphotypes of A. fraterculus have demonstrated that copulation duration is affected by female origin but not by male origin (Abraham et al. ), suggesting that copulation duration is under female control. Female‐mediated effects could have a stronger effect on copula duration than exposure to rival males.…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…The interpretation of the results in the case of D. melanogaster assumes that copulation duration is under male control (MacBean & Parsons ), while in our case, crosses between different morphotypes of A. fraterculus have demonstrated that copulation duration is affected by female origin but not by male origin (Abraham et al. ), suggesting that copulation duration is under female control. Female‐mediated effects could have a stronger effect on copula duration than exposure to rival males.…”
Section: Discussionsupporting
confidence: 41%
“…Alternatively, mating latency could be under female control (Abraham et al. ). Females could be detecting and copulating earlier when there are more males to choose from at the mating site, or they could be copulating earlier as a way to avoid male harassment at higher male densities.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual behaviour studies helped to identify behavioural characteristics that allowed distinct morphotype descriptions such as time of sexual activity, acoustical signals and sequence of courtship behaviour (Rull et al 2012, 2013, Devescovi et al 2014, Dias et al in press). One post-copulatory study revealed differences in sperm storage and remating propensity between the Peruvian and Brazilian 1 morphotypes (Abraham et al 2014). Hybrid females tended to mate with hybrid males and as a result Segura et al (2011) suggested that hybridization is a possible speciation mechanism.…”
Section: Situation Analysis At the Start Of The Crp And Ouputs For Eamentioning
confidence: 99%
“…Essa pode ser a mesma explicação do reconhecimento e preferência em acasalar com machos provenientes do mesmo fruto hospedeiro, uma vez que o reconhecimento de parceiros e "aparentados" se dá por meio da identificação de feromônios e hidrocarbonetos de cutícula. Outro fator que pode explicar a relação do fruto hospedeiro com a escolha do parceiro pela fêmea, é que a constituição química da dieta é um dos precursores da síntese de feromônios e dos hidrocarbonetos de cutícula (Rundle et al 2005 Os trabalhos sobre compatibilidade reprodutiva no complexo A.fraterculus envolvem populações de diferentes localidades (Selivon et al 1999;Vera et al 2006;Caceres et al 2009;Rull et al 2013;Abraham et al 2014;Dias et al 2015) ou criadas em laboratório (Dias et al 2015), esse é o primeiro trabalho que estuda a compatibilidade reprodutiva associada ao uso de diferentes hospedeiros com populações encontradas em simpatria.…”
Section: Iv3 Perturbações Ontogenéticas Associadas Ao Estresse Da Tunclassified